Establishing Critical Limits for Nickel in Soil and Plant for Predicting the Response of Spinach (Spinacia oleracea) - K.C. Patel; A.K. Shukla, Dileep Kumar*, V.P. Ramani (Journal of the Indian Society of Soil Science, 2021)
Nickel (Ni) is an essential element for plants and research reports are available indicating its beneficial effects on growth of higher plants as well. Though abundant information exists on Ni toxicity in soil and plant system but not much is available on its critical level of deficiency (CLD) in soils and plants. A pot experiment was conducted in net-house of the micronutrient research project, Anand Agricultural University, Anand, Gujarat. For assessing the critical limit in soil, three bulk soils viz., low (<0.5 mg Ni kg-1), medium (0.5 to 1.0 mg Ni kg-1) and high (>1.0 mg Ni kg-1) were collected from different locations of Anand district. Six levels of Ni, i.e. Ni0, Ni2, Ni4, Ni6, Ni8 and Ni10 (0, 2.0, 4.0, 6.0, 8.0 and 10.0 mg Ni kg-1 soil) were applied in all 20 soils (10 low, 6 medium and 4 high in Ni content in soil). The experiment was conducted in factorial completely randomized design with three replications. The critical limit of Ni in soil was determined by Bray’s per cent yield plotted against soil available Ni using the scattered diagram in graphical as well as statistical method. Wide variation in dry matter produce was observed across the soils. The concentration of Ni in spinach plant increased with increasing the level of Ni in soil. The CLD of the 0.005 M DTPA-CaCl2 extractable Ni in soil and plant was worked out as 0.46 and 2.27 mg kg-1, respectively with statistical method. Whereas, in graphical method it was reported as 0.50 and 2.20 mg kg-1, respectively in spinach crops.